Déficit público e taxa de inflação: testes de raiz unitária e causalidade para o Brasil -1991-1999 (Economia Aplicada, 2003)
This paper makes a brief revision of the concepts about public budget constraint in general and restrict aspects, such as nominal and primary public deficit. Some tests like the causality test; proposed by Granger are used to capture the relation between inflation, measured by IGP-DI (General indexes of Prices) and these concepts. Unit root tests are also applied to the series studied in this paper. The period ofinterest ranges from august, 1994 - after the implementation of the Real plan, to march, 1999 - after the change ofthe exchange rate regime. The results show that both nominal and primary public deficit caused inflation in the Real era, although the reverse is not true.